1986
DOI: 10.1172/jci112512
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 stimulates fibroblasts to produce granulocyte-macrophage colony-stimulating activity and prostaglandin E2.

Abstract: Granulocyte-macrophage colony-stimulating activty (GM-CSA) can be produced by a variety of normal cell types including mononuclear phagocytes, activated T lymphocytes, endothelial cells, and fibroblasts. Recent evidence shows that a major role of the monocyte-macrophage is the recruitment of environmental cells, i.e., fibroblasts, to produce GM-CSA. In this study we have identified interleukin 1 (IL-i) as a monokine that stimulates fibroblasts to produce and release GM-CSA and prostaglandin E2 (PGE2). Both pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(124 citation statements)
references
References 39 publications
8
114
0
2
Order By: Relevance
“…Accordingly, IL-1␣ increased their production and reduced this lag time and IL-1␣-prestimulated EC were more efficient in supporting this expansion than unstimulated cells. IL-1 is known to stimulate the secretion by EC of cytokines, some of them having functional importance in hematopoiesis such as IL-6, 60 colony-stimulating factors 61,62 or more recently LIF. 13,41 Although a direct effect of IL-1␣ on the progenitors cannot be ruled out, 63 our results suggest that it is mainly acting through the modulation of cytokine production by the stromal layer.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, IL-1␣ increased their production and reduced this lag time and IL-1␣-prestimulated EC were more efficient in supporting this expansion than unstimulated cells. IL-1 is known to stimulate the secretion by EC of cytokines, some of them having functional importance in hematopoiesis such as IL-6, 60 colony-stimulating factors 61,62 or more recently LIF. 13,41 Although a direct effect of IL-1␣ on the progenitors cannot be ruled out, 63 our results suggest that it is mainly acting through the modulation of cytokine production by the stromal layer.…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF, which can be produced by T lymphocytes, monocytes, fibroblasts, and endothelial cells (13)(14)(15), has been recognized to stimulate functions of mature eosinophils (16), including antibody-dependent cytotoxicity (17,18), synthesis of leukotriene C4 in response to calcium ionophore stimulation (17), and cell-surface expression of antigens granulocyte function antigen 1 (GFA-1) and Mol (18 longed eosinophil survival in culture (18), and its presence was required to maintain the viability of eosinophils cultured with 3T3 fibroblasts (7). Utilizing the coculture system with 3T3 fibroblasts and GM-CSF, we have shown that eosinophils during in vitro culture can express HLA-DR. Because both fibroblasts and GM-CSF were needed to maintain eosinophil viability in culture as noted before (7), the specific roles of GM-CSF and fibroblasts in eliciting HLA-DR expression by eosinophils could not be determined.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, all of them have been initially identified as products produced by the classical immune-inflammatory cells (lymphocytes and monocytes) upon appropriate conditions of stimulation [45,46]. However, it is now clear that this group of cytokines can also be produced by other cell types, particularly structural cells, including fibroblasts, epithelial, endothelial and smooth muscle cells [47][48][49][50][51][52]. It is of interest to note that optimal conditions for the synthesis of these cytokines require IL-1 and/or TNF-α stimulation.…”
Section: Cytokinesmentioning
confidence: 99%